Efektivitas Komitmen Manajemen Atas Kualitas Pelayanan Frontline Employees di Perguruan Tinggi - Rony Setiawan (Universitas Kristen Maranatha, 2016)
Customers have a very important role for the survival and progress of each organization. Service providers are internal customers while the service users are external customers. Harmonious interactions between the ability and willingnessof employees to provide services with the customer satisfaction in using the service, will become competitive advantages for organizations that provide services as theirmain business commodities. Universities, as one important part of the education industry, need to provide quality academic administrative services to students as their main customers. In order to realize this, universities need to have managementcommitment to service quality which is reflected through training, empowerment, compensation, management support, and technology. With the implementation ofthese programs, employees will be more motivated to work in providing excellent quality service to their customers. Organizations that have strong commitment ontheir high quality performances will get high quality employees and customers as well.Keywords: Management commitment to service quality, frontline employees, job satisfaction, prosocial service behavior